Lessons learnt while integrating services for children: qualitative interviews with professional stakeholders - Vanessa Baxter; Ewen Speed; Vasilios Ioakimidis; Matthew Ross (BMC, 2023)
Abstract Background In the English NHS, integrated care is seen as an opportunity to deliver joined-up care for children and families. This paper examines the lessons learnt by professional stakeholders in the process of developing different examples of integrated models of care/frameworks for children's services. Methods Initial desk research was undertaken to identify different examples of integrated care models and systems/frameworks for children's services. This identified forty-three examples in England. Of these, twelve examples were shortlisted after consultation with the senior managers within the Health and Care Partnership that had commissioned the research, and a more detailed online search for published documents was undertaken. Semi-structured qualitative interviews were then conducted with sixteen professional stakeholders in eight of these examples, ranging from one to four interviewees per example. Interviews focused on the lessons learnt from integrating and transforming services. Data were analysed using framework analysis. Results The eight examples vary in their design but have several broad commonalities. A number of common themes and learning have emerged, of which two were identified within all eight examples: the first is about focusing on children and young people; the second is about focusing on partner engagement and collaboration and the importance of building trust and relationships between partners. A number of other important themes also emerged together with several challenges. Conclusions A number of common factors were identified that are essential to success in integrating health and care systems. Common across all localities were being child-centric and focusing on child outcomes plus the importance of building trust, engagement and relationships with partners. The findings can help health and care system leaders transform services to ensure efficiency, improvement in services and integration.